FACTORS INFLUENCING THE SPIRITUAL WORLDVIEW OF AN INDIVIDUAL IN CYBERSPACE - Karimova Mukhlisa Azizbek qizi (Bright Mind Publishing, 2025)
This article examines the flaws that negatively affect the spiritual maturity of individuals in cyberspace, taking into account the ideological attacks that spread ideas of aggression, destruction, depravity, and immorality within the spiritual realm of individuals in today's globalization era.
Keywords: Digital technology, cyberspace, “virtual culture,” entertainment environment, modern society, “mass culture.”